A COMPARISON OF ZAKAT MANAGEMENT IMPLEMENTATION IN EAST LOMBOK, TEGAL AND PADANG PANJANG DISTRICTS - Suhartoyo, Faizal; Fauzan, Aris (istinbath, 2024)
This study aims to analyze the differences in the implementation of zakat management in three different regions, namely East Lombok, Tegal, and Padang Panjang districts. Different approaches, such as economic empowerment, information technology, and integration with local government programs, underlie the implementation of zakat in each region. The research method used is a qualitative approach with data collection through in-depth interviews and document analysis. The results of zakat implementation in the three regions reflect variations in community empowerment. In East Lombok Regency, the economic empowerment approach has successfully increased the economic independence of zakat recipients through business training. In Tegal, information technology is used to facilitate zakat collection and distribution, creating efficiency and transparency. In Padang Panjang, the integration of zakat with local government programs resulted in the synergy of broader empowerment. The determinants of successful implementation include regional context, commitment to zakat institution, and community participation. Similar research by Muhammad Zumar Aminudin, Lila Pangestu Hadiningrum (2019) has described zakat approaches in different contexts, providing in-depth insights into variations in zakat implementation. The theoretical implication of this research highlights the importance of a contextual approach in zakat implementation. The practical implication provides guidance for zakat institutions, local governments, and communities in improving the effectiveness of zakat programs. In conclusion, the successful implementation of zakat requires an in-depth understanding of regional characteristics, selection of appropriate approaches, and adaptation to social and economic dynamics.